DC and RF characteristics of 20 nm gate length InAlAs/InGaAs/InP HEMTs for high frequency application - Amin Boursali; Ahlam Guen-Bouazza; Choukria Sayah (International Journal of Electrical and Computer Engineering (IJECE), 2020)
lnAlAs/lnGaAs/InP high electron mobility transistor (HEMT) offers excellent high frequency operation.In this work,the DC and RF performance of a 20 nm gate length enhancement mode InAlAs/InGaAs/InP high electron mobility transistor (HEMT) on InP substrate are presented.The SILVACO-TCAD simulations performed at room temperature using the appropriate model sshowed that the studied device exhibit excellent pinch-off characteristics, with a maximum transconductance of 1100ms/mm, a threshold voltage of 0,62V, and an Ion/Ioff ratio of 2.106. The cut-off frequency and maximum frequency of oscillation are 980 GHz and 1.3THz respectively. These promising results allow us to affirm that this device is intended to be used in high frequency applications.